1995
DOI: 10.1002/1098-108x(199501)17:1<51::aid-eat2260170107>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, total energy expenditure, and food intake in grossly obese and normal weight women

Abstract: The doubly labeled water method was used to measure average daily total energy expenditure (TEE) in 10 healthy normal weight women classified as unrestrained eaters and in 10 grossly obese women. The body mass index was 20.0 ± 1.3 kg/m2 in the control group and 37.4 ± 8.1 kg/m2 for the obese group. TEE was measured over a 2‐week period. TEE was 2,357 ± 504 kcal/day for the controls and 3,708 ± 367 kcal/day for the obese group during a cognitive‐behavioral treatment. © 1995 by John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
0
15
2
Order By: Relevance
“…Whereas a decrease in the ability of slightly subclinically depressed subjects to rate fat concentrations accurately when in negative or positive mood has not previously been reported, others have shown that obese people underestimate their energy and fat intake [35][37]. In the present sample, the correlation between depression score (BDI) and body mass (BMI) was r  = 0.400 (p = 0.007) for the subjects in the group with the sub-clinical mild depression.…”
Section: Discussioncontrasting
confidence: 63%
“…Whereas a decrease in the ability of slightly subclinically depressed subjects to rate fat concentrations accurately when in negative or positive mood has not previously been reported, others have shown that obese people underestimate their energy and fat intake [35][37]. In the present sample, the correlation between depression score (BDI) and body mass (BMI) was r  = 0.400 (p = 0.007) for the subjects in the group with the sub-clinical mild depression.…”
Section: Discussioncontrasting
confidence: 63%
“…Mean under-reporting by the non-diet-resistant group in the Lichtman et al (1992) study was much less than in the present study. However, most studies showed similar (36%, Black et al (1993); 33%, Prentice et al (1986)) or greater under-reporting (46 -59%; Platte et al (1995); Buhl et al (1995); Lichtman et al (1992)) than in the present study. Although it does appear clear that obese and previously obese women routinely under-report their energy intake, the magnitude of underreporting, and the corresponding contributing factors, are not clear.…”
Section: Discussioncontrasting
confidence: 58%
“…Other studies in obese subjects have shown a range of energy intake under-reporting of 33 -47% relative to TEE measured by the doubly labeled water method (Prentice et al, 1986;Lichtman et al, 1992;Buhl et al, 1995;Platte et al, 1995). Under-reporting of energy intake of 11 and 32% has been shown in lean, athletic women (Schulz et al, 1992;Edwards et al, 1993) compared to doubly labeled waterdetermined TEE.…”
Section: Introductionmentioning
confidence: 98%
“…The contrary was the case. We observed a negative trend in both groups (RS: r = − 0.28, p = ns; DD: r = − 0.03, p = ns), suggesting a problem with food intake and weight gain or a problem with the validity of the food diaries [ 16 ] . A signifi cant diff erence was found in feeding time per day.…”
Section: Discussion ▼mentioning
confidence: 79%